Over‐expression and potential role of cyclophilin A in human periodontitis. (27th February 2013) - Liu, L.; Li, C.; Xiang, J.; Dong, W.; Cao, Z.
Abstract : Background and Objective: We previously demostrated that EMMPRIN participates in the periodontitis and its interaction with Cyclophilin A possibly exists in animal periodontitis models. This study is aimed to address the expression and potential role of cyclophilin A (CypA) in human periodontitis. Material and Methods: Gingival tissues and peripheral blood were collected from patients with moderate to severe periodontitis or from healthy donors. Western blotting and immunohistochemistry were performed to detect the expression and distribution of CypA in the gingival tissues. Peripheral blood mononuclear cells (PBMCs) and neutrophils were isolated from the peripheral blood by Ficoll–Paque density‐gradient centrifugation. Chemotaxis assays were applied to evaluate the effects of different concentrations of CypA (100, 300 and 500 ng/mL) on the migration of PBMCs and neutrophils. Supernatants of human THP‐1 cells were collected after treatment with 200 ng/mL of CypA for different periods of time (1, 3, 6, 12 and 24 h) to detect the levels of interleukin (IL)‐1β, IL‐8 and tumor necrosis factor alpha (TNF‐α) by ELISA. Results: Western blot analyses revealed an increase of CypA expression in inflamed gingival tissues compared with healthy tissues. Immunohistochemistry identified that the over‐expressed CypA was localized in the infiltrating cells and/or in the extracellular matrix in the inflamed gingival connective tissues. The positive infiltrating cells contained mononuclear cells and lobulated‐nuclei neutrophils. Chemotactic assays showed that 300 ng/mL of CypA apparently facilitated the chemotaxis of PBMCs/neutrophils from healthy donors, compared with the no‐treatment control ( p < 0.01 for PBMCs, p < 0.05 for neutrophils), whereas 100 and 500 ng/mL of CypA only weakly enhanced the chemotaxis of PBMCs/neutrophils ( p > 0.05 for PBMCs/neutrophils, not significant). The PBMCs/neutrophils from patients with periodontitis exhibited a stronger ability to migrate when stimulated with 300 ng/mL of CypA than did PBMCs/neutrophils from healthy donors ( p < 0.05 for PBMCs, p < 0.01 for neutrophils). ELISA revealed that the level of TNF‐α secreted by THP‐1 cells was elevated after treatment with 200 ng/mL of CypA for 12 h compared with the no‐treatment 0‐h control ( p < 0.05). The IL‐8 level was sharply raised after 3 h of stimulation with 200 ng/mL of CypA ( p < 0.01 compared with 0 h), but no significant change was observed at the other time points ( p > 0.05). There was no statistical difference at any of the treatment time points for the secretion of IL‐1β ( p > 0.05 for 1, 3, 6, 12 and 24 h compared with 0 h). Conclusions: CypA participates in the pathogenesis of human periodontitis. It may be involved in the inflammatory response of periodontal tissues through inducing the chemotaxis of PBMCs/neutrophils and the secretion of TNF‐α/IL‐8.